Ecological Impacts of Toxic Chemicals - Sánchez-Bayo, Francisco; Brink, Paul J. van den; Mann, Reinier M. (Bentham Science Publishers, 2011)
Ecological Impacts of Toxic Chemicals presents a comprehensive, yet readable account of the known disturbances caused by all kinds of toxic chemicals on both aquatic and terrestrial ecosystems. Topics cover the sources of toxicants, their fate and distribution through the planet, their impacts on specific ecosystems, and their remediation by natural systems. Each chapter is written by well-known specialists in those areas, for the general public, students, and even scientists from outside this field. The book intends to raise awareness of the dangers of chemical pollution in a world dominated by industry and globalization of resources. Because the problems are widespread and far reaching, it is hoped that confronting the facts may prompt better management practices at industrial, agricultural and all levels of management, from local to governmental, so as to reduce the negative impacts of chemical contaminants on our planet.